Onset of Small-World Behavior in Topologically Evolving Networks - Juanico, D. E.; Monterola, C. P.; Saloma, C. A. (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
We evolve topology of a network of N fully-coupled nodes that interact according to repulsion-attraction dynamics within a confining wall. The dynamics portrays each node’s tendency to keep distance from its competitors while maintaining a lighter tendency to resist relative isolation. Each node is characterized by two parameters: an intrinsic mobility µ and a preferred neighboring distance ρ. Onset of clustering is found to occur at a critical variance in mobility, σµ 2 = 1, and in preferred neighboring distance, σµ 2 = 10. This result implies that small-world behavior manifested in clustering can be triggered by the diversity of node population.